Capital Accumulation, Asset Price Dynamics and the Macroeconomy: A Dependent Economy Model. Issue 3 (August 2018) - Basu, Moumita; Nag, Ranjanendra Narayan
This article develops a dependent economy model of determination of employment and asset prices that integrates the roles of relative prices, expectations and dynamics of capital accumulation. In this model, money wage is rigid which leads to persistence of unemployment. Labour and capital are used as factors of production in the traded sector while the non-traded sector uses labour and imported intermediate inputs. The article examines macroeconomic implications of selective economic reforms for asset price dynamics, growth and employment. The discussion of comparative static exercises shows that not only the effects of different policies are ambiguous but also the short-run and the long-run effects are qualitatively different. For example, tariff liberalization causes the short-run expansions of both traded and non-traded sectors but overtime it may depress the capital stock leading to contraction of both the sectors and an increase in unemployment. The broad message of this article is that the design of macroeconomic policy should not be purely based on considerations of the short-run effects of policy changes. JEL: E22, F13, F41